Selective Patterns of Cognitive Impairment in Spinocerebellar Ataxia Type 6 and Idiopathic Late-Onset Cerebellar Ataxia - Rentiya, Zubir S; Jung, Brian C; Bae, Junun; Liszewski, Christine M; Fishman, Ann; Du, Annie X; Margolis, Russell L; Ying, Sarah H (Archives of clinical neuropsychology, 2018)
Abstract Purpose To determine cognitive impairment patterns in patients with spinocerebellar ataxia type 6 (SCA6) compared to patients with idiopathic late-onset cerebellar ataxia (ILOCA). Methods Neurocognitive testing was conducted on 21 SCA6, nine ILOCA, and 27 controls subjects. Intergroup differences were assessed using the Wilcoxon signed-ranked test or Student’s t-test. Principal component analysis (PCA) was performed on nine cognitive variables, and Hotelling’s T-squared test assessed group-specific differences. Pearson’s correlations assessed changes in cognitive performance and disease progression. Intra-group differences among SCA6 were examined in a post-hoc analysis. Results SCA6 and ILOCA patients showed impairment in visuo-spatial executive function, phonemic verbal fluency, and semantic-verb word generation. ILOCA showed impairment in mental flexibility/response inhibition, verbal learning, semantic-noun verbal fluency, and forward numerical working memory. Within the first three principal components, SCA6 and ILOCA differed from controls and from each other. Verbal working and immediate visuo-spatial memory correlated with disease duration for SCA6. For ILOCA, Mini-Mental Status Exam and RCF copy correlated with disease duration. Conclusion Differing patterns of cognitive dysfunction were seen in SCA6 and ILOCA. PCA suggested that distinct SCA6 subgroups may exist, SCA61 with significant ILOCA overlap in several cognitive deficits, and SCA62 showing deficits in visuo-spatial performance only.